Multifractality of climate networks - A. J. Thomas; J. Kurths; D. Schertzer; D. Schertzer (Nonlinear Processes in Geophysics)
Geophysical fields are extremely variable over a wide range of space–time scales. More specifically, they are intermittent in the sense that the strongest fluctuations are increasingly concentrated in sparser and sparser fractions of the space–time domain. Multifractals have been developed to analyze and simulate intermittency across scales, while climate networks can detect and characterize extreme-event synchronization. In contrast to multifractal analysis, climate networks are usually generated at a given observation scale despite displaying complex structures over larger scales and being likely to exhibit similar complexity at smaller scales.